2011
DOI: 10.1002/bjs.7804
|View full text |Cite
|
Sign up to set email alerts
|

Fenestrated endovascular aneurysm repair

Abstract: FEVAR for repair of suprarenal and juxtarenal aneurysms is a viable alternative to open repair. However, there is no level 1 evidence for FEVAR, and current evidence is weak with many unanswered questions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
72
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(73 citation statements)
references
References 32 publications
0
72
1
Order By: Relevance
“…Some designs are without fenestrations but with branches (pre-attached limbs or cuffs) targeted for the visceral aortic vessels, suitable for the endovascular treatment of thoracoabdominal aortic aneurysms (TAAAs). At least for short-necked and juxtarenal aortic aneurysms (JRAs), fenestrated stent-grafting technology has been shown to be feasible, [12][13][14][15][16][17][18][19][20] with published results of highvolume experienced single centers [21][22][23][24][25][26][27][28][29][30][31] and a few recent multicenter trials 32,33 sharing remarkable short-and midterm results, with the durability of the technique being satisfactory (technical success > 95%, low mortality rates averaging 1-2% and low rates of mid-term branch vessel occlusion averaging 4-9%). [25][26][27][28][29]34 Other imaginative procedures have also been developed or modified to allow for the segmental or complete coverage of the aorta in the region of vital branches, including the 'chimney', 'snorkel', 'periscope' [35][36][37] and combined endovascular exclusion and extra-anatomic mesenteric/renal bypasses (hybrid visceral revascularization).…”
mentioning
confidence: 99%
“…Some designs are without fenestrations but with branches (pre-attached limbs or cuffs) targeted for the visceral aortic vessels, suitable for the endovascular treatment of thoracoabdominal aortic aneurysms (TAAAs). At least for short-necked and juxtarenal aortic aneurysms (JRAs), fenestrated stent-grafting technology has been shown to be feasible, [12][13][14][15][16][17][18][19][20] with published results of highvolume experienced single centers [21][22][23][24][25][26][27][28][29][30][31] and a few recent multicenter trials 32,33 sharing remarkable short-and midterm results, with the durability of the technique being satisfactory (technical success > 95%, low mortality rates averaging 1-2% and low rates of mid-term branch vessel occlusion averaging 4-9%). [25][26][27][28][29]34 Other imaginative procedures have also been developed or modified to allow for the segmental or complete coverage of the aorta in the region of vital branches, including the 'chimney', 'snorkel', 'periscope' [35][36][37] and combined endovascular exclusion and extra-anatomic mesenteric/renal bypasses (hybrid visceral revascularization).…”
mentioning
confidence: 99%
“…A systematic review by Nordon et al 51 reported that non-RCTs were identified and they included eight cohort studies reporting 368 fEVAR cases and 12 cohort studies reporting 1164 OSRs of JRAAs. One systematic review by Cross et al 52 identified 11 fEVAR studies describing 660 procedures with no comparison. However, this study also acknowledged in its conclusions that 'there are currently no controlled trials comparing fEVAR with OSR, and current evidence is weak with many unanswered questions'.…”
Section: Chapter 7 Discussionmentioning
confidence: 99%
“…However, this study also acknowledged in its conclusions that 'there are currently no controlled trials comparing fEVAR with OSR, and current evidence is weak with many unanswered questions'. 52 Another systematic review included five single-arm studies on fEVAR and seven studies on OSR (one prospective and six retrospective). 4 They also identified and included a study in the form of an abstract that compared the results of fEVAR with those of OSR.…”
Section: Chapter 7 Discussionmentioning
confidence: 99%
“…Standard EVAR with infra-renal fi xation is possible with a less than 10 mm neck, but a higher rate of intraoperative and late complications can be expected [ 4 ] . Fenestrated EVAR (FEVAR) is a technically challenging endovascular alternative with a 30-day pooled mortality of 2 % [ 10 ] . Currently these are usually customized to individual patient anatomy creating a signi fi cant delay to treatment ( Fig.…”
Section: Alternative Treatment Optionsmentioning
confidence: 99%